Serum Bactericidal Antibody Responses of Adults Immunized with the MenB-4C Vaccine against Genetically Diverse Serogroup B Meningococci - Giuntini, Serena (Clin Vaccine Immunol, 2017)
MenB-4C is a meningococcal vaccine for the prevention of serogroup B disease. The vaccine contains factor H binding protein (FHbp) and three other antigens that can elicit serum bactericidal antibodies (SBA). For vaccine licensure, efficacy was inferred from the SBA responses against three antigen-specific indicator strains. The relation between those results and broad protection against circulating genetically diverse strains is not known. Twenty adults were immunized with two doses of MenB-4C given 1 to 2 months apart. SBA activity against 3 reference strains and 15 serogroup B test strains (6 from college outbreaks) was measured. Compared to the preimmunization titers, 70%, 95%, and 95% of subjects had ≥4-fold increases in the titers of anti-PorA P1.4, anti-NadA, and anti-FHbp antibodies against the reference strains, respectively. In contrast, only 25 to 45% of the subjects had ≥4-fold increases in responses to 10 of the 15 test strains, including 8 that expressed one to three of the antigens in the vaccine. At 1 month, the majority of subjects with <4-fold titer increases had serum titers of ≥1:4, which are considered sufficient for protection. However, the titers against four strains declined to <1:4 by 4 to 6 months in one-third to greater than 50% of the subjects tested. Clinically relevant isolates are often more resistant to SBA than the indicator strains used to measure antigen-specific SBA. A working model is that the percentage of subjects with titers of ≥1:4 at 1 month postimmunization correlates with short-term protection against that strain, whereas the percentage of subjects with ≥4-fold titer increases represents a more robust response. (The protocol used at the Oxford Vaccine Group has been registered at ClinicalTrials.gov under registration no. NCT02398396.)